Socio-economic impact of marine litter for remote oceanic islands: the Azores archipelago - González, Yasmina Maria Rodríguez (2021)
Marine litter is present throughout the world's oceans, representing a significant threat to marine ecosystems. While most efforts have focused on assessing ecological impacts, information on the socio-economic dimension of marine litter is scarce. Here we provide a detailed assessment of the direct economic costs of marine litter for a remote region of the North-East Atlantic, the Azores archipelago. Face-to-face interviews were performed to quantify and characterise the costs of marine litter-related incidents and coastal clean-ups to259 sea-users (fishermen, tourist operators and transport companies) and the costs of coastal clean-ups to 21 local authorities (parish councils, municipalities and harbours). We provide a detail characterisation of the frequency, type and costs of marine litter-related incidents and clean-ups along with an evaluation of the perceptions and opinions of different stakeholders on this issue. The average cost of a marine litter-related incident was €1618 (±401, SE), while the average cost associated with cleaning a coastal site was €10233 (±3597, SE) per local authority and year. Overall, marine litter pollution was estimated to cost a total of €710,698 (±195,181; SD) per year, which is the equivalent to 0.02% of the Gross Domestic Product of the Azores archipelago. Our results demonstrate that marine litter can significantly impact the activity of sea-users and represent an important economic burden for local authorities, thus, marine litter creates costs and inconveniences for a range of stakeholders engaged in marine activities and also increases the waste clean-up budgets of small communities living on remote islands. Quantifying the socio-economic implication of marine litter is crucial to further raise public awareness on this issue and demonstrate that the impacts are wide-ranging. O lixo marinho é qualquer material duradouro, fabricado ou processado que é descartado, eliminado ou abandonado na costa ou no mar. Dos diferentes tipos de lixo marinho, os plásticos são sem ...